Against empathy voice and authenticity - Lather, Patti (Kvinder, Køn & Forskning, 2000)
This paper asks what it is to claim empathy, voice and authenticity as the grounds of feminist research. It explores representational practices that refuse such grounds by residing in both situated and constantly changing intersections of interpretation, interruption and mutuality. The typical investments and categories of ethnography are challenged so as to put under theoretic pressure the claims of scientificity. Grounded in a study of women living with HIV/AIDS, also challenged is the ethnographer as "the one who knows" whose task is to produce the persuasive text the elicits reader empathy. Finally, the paper probes what is at work in the concepts of "voice" and "authenticity" in ethnographic work.